Injectable hydrogel as well as preparation method and application thereof

High-energy ray cross-linking of polymers without agents forms safe, controllable injectable hydrogels, addressing safety issues in existing fillers and enhancing longevity and efficacy for cosmetic and medical uses.

CN119161607APending Publication Date: 2024-12-20LIANGZHU LAB
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411058882.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing injectable hyaluronic acid fillers face safety issues due to toxic or carcinogenic cross-linking agents, which persist in the body and compromise long-term efficacy, necessitating a safer and more effective method for preparing hydrogels for cosmetic and medical applications.

Method used

A method involving high-energy ray cross-linking of polymers to form hydrogels without using cross-linking agents or organic solvents, followed by dilution to create injectable hydrogels using a small-caliber syringe, ensuring safety and controllable properties.

Benefits of technology

The method produces hydrogels with improved safety, controllable properties, and enhanced longevity, suitable for cosmetic and medical applications, maintaining shape and moisture without toxic residues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161607A_ABST
    Figure CN119161607A_ABST
Patent Text Reader

Abstract

The invention provides injectable hydrogel as well as a preparation method and application thereof, the preparation method comprises the following steps: utilizing energy generated by high-energy rays to enable macromolecules to be subjected to covalent cross-linking to form hydrogel, and carrying out thinning treatment to enable the hydrogel to be injected and extruded by a small-caliber syringe needle. No cross-linking agent or organic solvent is added in the whole hydrogel preparation process, so that the hydrogel has relatively high safety; in addition, the hydrogel prepared by the preparation method has excellent physical and chemical properties (water-retaining property, formability, degradation time, storage modulus and solid content) and stable batches, and is very suitable for the field of medical cosmetology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogel preparation, and in particular to an injectable hydrogel and a preparation method and application thereof. Background Art

[0002] As people age, the human body gradually shows morphological changes and physiological attenuation under the comprehensive regulation of endogenous and exogenous factors. Tissue fillers can be used to enhance tissues that may suffer volume loss due to fat malnutrition, pathological atrophy, and trauma, or used in the fields of facial plastic surgery, skin beauty, and body shaping, including eye plastic surgery, nose plastic surgery, lip plastic surgery, ear and eyebrow plastic surgery, facial contour plastic surgery, breast augmentation, buttock augmentation, etc. Tissue fillers used by injection can repair and correct the shape of soft tissues in a non-surgical way and have received widespread attention.

[0003] The most widely used injectable filler material at present is hyaluronic acid (sodium hyaluronate), which has a significant instantaneous filling effect. However, due to the presence of human hyaluronidase, exogenous sodium hyaluronate is maintained in the body for too short a time, making it difficult to achieve a long-term shaping effect. In order to increase the clinical use effect of hyaluronic acid, existing products have extended the degradation time of hyaluronic acid by cross-linking, such as "Juvederm", "Haiwei" and "Ailiwei", that is, different cross-linking agents are used to connect sodium hyaluronate molecules to form a network structure, thereby improving the stability of hyaluronic acid in the body. Existing cross-linked sodium hyaluronate gel products mostly use divinyl sulfone (DVS), 1,4-butanediol diglycidyl ether (BDDE), etc. as cross-linking agents. However, the above cross-linking agents are mostly toxic or carcinogenic, and the cross-linking agents are wrapped in the cross-linked sodium hyaluronate gel and are difficult to remove. As hyaluronic acid degrades, residual cross-linking agents enter the body, which will cause great risks. Some recent studies have used safer cross-linking agents. For example, Chinese patent CN 104761734 B discloses a method of cross-linking hyaluronic acid using lysine. However, in the preparation process of this material, toxic solvents and small molecules are still used, and there are still potential safety hazards.

[0004] Therefore, there is an urgent need to find a safer and more effective method for preparing injectable hydrogels. The prepared injectable hydrogels can be used to prepare hydrogel tissue fillers to meet the needs of facial plastic surgery, skin beauty, and body shaping. Summary of the invention

[0005] The present invention provides an injectable hydrogel and a preparation method and application thereof. The preparation method utilizes the energy generated by high-energy rays to cause covalent cross-linking of polymers to form a hydrogel, and then thins the hydrogel so that it can be injected and extruded using a small-caliber syringe needle. The entire hydrogel preparation process does not involve the use of any cross-linking agent or organic solvent, so it has high safety.

[0006] On the one hand, the present invention provides a method for preparing an injectable hydrogel by diluting a non-injectable hydrogel to prepare an injectable hydrogel; the non-injectable hydrogel is obtained by irradiation crosslinking; the injectable hydrogel refers to a hydrogel in a liquid state that can be extruded or injected through a needle, and the hydrogel can be in a liquid or solid state after extrusion or injection; the non-injectable hydrogel refers to a hydrogel in a solid state that cannot be extruded or injected through a needle.

[0007] The dilution treatment in the present invention means that the non-injectable hydrogel obtains injectable properties, which can be achieved by partially breaking the covalent bonds inside the hydrogel and reducing the solid content.

[0008] A hydrogel refers to a water-rich polymer network, and its state cannot be described simply as "solid" or "liquid". In fact, a hydrogel has both solid and liquid characteristics, and the state of the hydrogel can be defined by rheological parameters. Among them, the "storage modulus" (G') reflects the "solid" characteristics, and the "loss modulus" (G") reflects the "liquid" characteristics. When G'>G", the hydrogel behaves more like a "solid", and when G">G', the hydrogel behaves more like a "liquid". Injectable hydrogels are divided into two types. One is that the hydrogel behaves more like a "liquid" in any state, and the other is that the hydrogel behaves more like a "solid" in the unloaded state and more like a "liquid" when subjected to shear force (such as through a narrow syringe needle), so it can also be injected. The latter injectable hydrogel has the property of "shear thinning". When not subjected to shear force, G'>G" of the hydrogel, showing as a solid. When subjected to shear force, G"<G' of the hydrogel, showing as a fluid, so it can be extruded from the syringe needle. After the extrusion is completed, the hydrogel is no longer subjected to shear force, and thus returns to the state of G'>G", that is, it shows as a solid again.

[0009] The property of "shear thinning" has a theoretical basis in polymer physics. Briefly speaking, in ordinary hydrogels (non-injectable hydrogels), there are interconnected polymer networks, and the activities of the polymers are restricted. In hydrogels with the property of "shear thinning" (injectable hydrogels), the polymer chains have a certain degree of mobility. When subjected to shear force, the polymer chains can move parallel to the direction of the shear force, that is, when the polymer chains pass through a narrow space such as a syringe needle, they can form a consistent orientation. Macroscopically, it shows a decrease in viscosity, a decrease in G', and an increase in G", and can be injected and extruded. After the shear force disappears, the polymer chains return to a random orientation, macroscopically showing an increase in viscosity, an increase in G', and a decrease in G", and the shape remains stable. Further, the non-injectable hydrogel needs to be diluted to prepare an injectable hydrogel; the needle is a small-caliber needle, and the inner diameter of the small-caliber needle is less than 21G.

[0010] Furthermore, the thinning treatment includes crushing the non-injectable hydrogel and mixing it with water. The needle is a small-caliber needle, which has a smaller inner diameter than a 21G needle.

[0011] It is understandable that it is easier for hydrogel to pass through a large-caliber needle, but it is more difficult to pass through a small-caliber needle, because the smaller the needle, the higher the requirements for hydrogel fluidity, viscosity and other properties. The larger the number, the smaller the inner diameter of the needle. For example, the needle of a 5mL syringe is 21G, and the needle of a 1mL syringe is 25G.

[0012] Furthermore, the non-injectable hydrogel is obtained by cross-linking a polymer aqueous solution through radiation.

[0013] There are two types of cross-linking: physical cross-linking and chemical cross-linking. Physical cross-linking is to make polymer molecules interpenetrate each other through physical action to form a macromolecular structure without changing the chemical structure of the original molecules; while chemical cross-linking is to form covalent bonds through chemical reactions to form new macromolecular polymer structures. In order to cause chemical reactions, chemical cross-linking agents are often added, such as peroxide cross-linking agents, silane cross-linking agents and azo cross-linking agents, etc. However, the products generated by these cross-linking agents have more or less adverse effects on the human body or the environment.

[0014] Two types of sodium polyglutamate sols were prepared by irradiation and chemical agents, respectively. It was found that the water retention and transmittance of irradiated sodium polyglutamate hydrogel were higher than those of chemical cross-linking. High water retention means better moisturizing and water-locking performance. When used as a medical beauty injection, it can maintain the filling effect for a longer time and keep the filled part elastic; injection products with high transmittance are more beautiful and highly accepted by users. In addition, transmittance is an indicator of the uniformity of the hydrogel, that is, the higher the transmittance, the more uniform the hydrogel. Therefore, after injection, the touch of the filled part can be guaranteed to be uniform. In addition, irradiation does not involve the addition of any cross-linking agent or organic solvent, and it is also a widely recognized sterilization method. In short, irradiation is preferred to generate sodium polyglutamate hydrogel.

[0015] Furthermore, the polymer includes one or more combinations of sodium polyglutamate, sodium hyaluronate, carboxymethyl cellulose, polyethylene oxide, sodium alginate, and sodium carboxymethyl starch.

[0016] There are certain differences in the physicochemical properties of the injectable hydrogels prepared by irradiation hydrogels with different polymer components after dilution. Compared with irradiation cross-linked carboxymethyl cellulose hydrogel, irradiation cross-linked sodium polyglutamate hydrogel lost 10% less water after three days of natural placement. This may be because carboxymethyl cellulose belongs to a polysaccharide structure, and there is a sugar ring structure with large steric hindrance in the molecular chain, which leads to a high viscosity of the aqueous solution of carboxymethyl cellulose, and thus it is impossible to obtain a carboxymethyl cellulose aqueous solution with high solubility. Due to the low concentration, the carboxyl content in the final product is also low; on the other hand, during irradiation, sufficient cross-linking cannot occur in the carboxymethyl cellulose aqueous solution, and even the carboxymethyl cellulose hydrogel prepared under high irradiation dose conditions cannot be obtained by dilution to obtain an injectable hydrogel with good formability. Compared with sodium hyaluronate hydrogel, sodium polyglutamate hydrogel has a better filling and molding effect. In summary, compared with the above two hydrogels, sodium polyglutamate hydrogel is more suitable for cosmetic filling.

[0017] In addition, adding some high molecular compounds based on sodium polyglutamate as the basic raw material can improve the performance of the gel to varying degrees, especially the water retention rate, among which adding sodium hyaluronate has the best effect.

[0018] Furthermore, the molecular weight of the sodium polyglutamate is 100,000-2,000,000; the molecular weight of sodium hyaluronate is 200,000-3,000,000; the molecular weight of carboxymethyl cellulose is 5,000-1,000,000; the molecular weight of polyethylene oxide is 50,000-100,0000; the molecular weight of sodium alginate is 5,000-100,000; and the molecular weight of sodium carboxymethyl starch is 10,000-1,000,000.

[0019] Furthermore, the polymer includes sodium polyglutamate. Preferably, the molecular weight of sodium polyglutamate is 700,000 to 2,000,000;

[0020] Furthermore, the concentration of the sodium polyglutamate aqueous solution is 5% to 50%, the concentration of the sodium hyaluronate aqueous solution is 5% to 15%, the concentration of the carboxymethyl cellulose aqueous solution is 2% to 30%, the concentration of the polyethylene oxide aqueous solution is 5% to 30%, the concentration of the sodium alginate aqueous solution is 2% to 10%, and the concentration of the sodium carboxymethyl starch aqueous solution is 5% to 30%.

[0021] Furthermore, nitrogen needs to be introduced into the polymer aqueous solution before radiation cross-linking to exhaust oxygen in the polymer aqueous solution.

[0022] Furthermore, the radiation crosslinking is performed by electron beam irradiation or cobalt 60 irradiation.

[0023] Further, the radiation cross-linking dosage is 5-200 kGy. Preferably, the radiation cross-linking dosage is 70-130 kGy.

[0024] Furthermore, the method for thinning the non-injectable hydrogel includes one or more of the following:

[0025] The first method: Use a mixing syringe to mix the non-injectable hydrogel and water in the mixer and push them together to mix evenly;

[0026] The second method is to squeeze the non-injectable hydrogel through a sieve and then stir and mix it in water;

[0027] The third method is to dry the non-injectable hydrogel, grind it, and then mix it with water;

[0028] The fourth method is to sterilize the non-injectable hydrogel by wet heat sterilization and then stir and mix it evenly in water.

[0029] In some embodiments, the first method (pushing in a mixer) is preferably used to break up the non-injectable hydrogel.

[0030] The above-mentioned dilution methods can all be used to prepare injectable hydrogels, but there are differences in the prepared products. Among them, the quality of hydrogels diluted with a mixing syringe is the most stable between batches. This may be because the steps of this method are the simplest and are completed entirely in a sealed syringe without the need for transfer, canning, etc., which is not easy to lose and easy to control quality.

[0031] Compared with other thinning methods, the injectable hydrogel prepared by the mixed syringe mutual pushing method has better injectability and formability, and the storage modulus and solid content of the hydrogel are the most stable.

[0032] Furthermore, the volume ratio of the non-injectable hydrogel of the first, second or fourth type to water is 1:0.5-1:10.

[0033] Furthermore, the mesh size of the second sieve is 50-300 mesh.

[0034] The mesh number corresponds to the aperture of the sieve. For sieves with a mesh size of more than 300, the aperture is less than 50 microns, making it difficult to squeeze through; for sieves with a mesh size of less than 50, the hydrogel is not sufficiently broken and the gel cannot obtain injectable properties.

[0035] Furthermore, the mass ratio of the third non-injectable hydrogel to water is 1:100-1:20.

[0036] In another aspect, the present invention provides an injectable hydrogel, wherein the injectable hydrogel is prepared by the method described above.

[0037] In yet another aspect, the present invention provides use of the injectable hydrogel as described above for preparing a hydrogel tissue filler.

[0038] In some embodiments, the hydrogel tissue filler is mainly used in the fields of facial plastic surgery, skin beauty, body shaping, etc.

[0039] The parameter adjustment process is to make the injectable hydrogel show different properties after injection according to the actual use requirements of the injectable tissue filler. In some use scenarios, such as filling the corners of the eyes and wrinkles, the filler needs to have good fluidity, while in some use scenarios, such as rhinoplasty, forehead plastic surgery, mandibular plastic surgery, etc., the filler needs to maintain its shape for a long time after injection.

[0040] Therefore, among all the parameters that need to be adjusted, the irradiation dose is the most critical. The irradiation dose actually changes the degree of cross-linking of the hydrogel. When the irradiation dose is low, the degree of cross-linking of the hydrogel is insufficient, and when the solid content is too high, it cannot be injected and extruded. When the hydrogel is injected through thinning treatment, the resulting hydrogel is more like a "liquid" in any state and has better fluidity after injection. When the irradiation dose is increased to above 70kGy, the degree of cross-linking of the hydrogel is neither high nor low. Through thinning treatment, the "shear thinning" performance can be obtained, and it has better formability after injection. When the irradiation dose is increased to above 200kGy, the degree of cross-linking of the hydrogel is too high, and no matter how it is thinned, it can no longer be extruded through a syringe. At this time, even if the hydrogel is broken into fine particles, it cannot pass through a small-caliber syringe needle.

[0041] The above-mentioned thinning operation is crucial for the injectability of the hydrogel. Thinning is not simply swelling the hydrogel to reduce the solid content of the hydrogel. Extruding the hydrogel through a small-caliber syringe needle requires reversible chemical bonds or forces inside the hydrogel, and simple swelling does not destroy the polymer covalent bond network inside the hydrogel, and thus cannot achieve the injectable effect. Through mechanical crushing or wet heat treatment, the polymer covalent bond network inside the hydrogel is destroyed, and the macroscopic hydrogel with a destroyed polymer network reconnects to each other through non-covalent interactions to produce a self-healing effect. The newly formed non-covalent bonds have weaker forces, and the formation and breaking of these bonds are reversible processes, which is conducive to the polymer chains forming a more consistent orientation under the action of shear force, so that they can be squeezed out of a small-caliber syringe needle.

[0042] At a specific irradiation dose, the adjustment of the initial concentration and the dilution ratio cooperate with each other to obtain an injectable state, but do not determine the fluidity or formability of the hydrogel after injection. For example, at an irradiation dose of 20k, no matter how the initial concentration and the dilution ratio are adjusted, only a hydrogel with good fluidity but poor formability can be obtained. When the initial concentration is high (for example, 20%), a higher dilution ratio is required to make it injectable, and when the initial concentration is low (for example, 10%), a lower dilution ratio is required to make it injectable. The initial concentration needs to be higher than a certain value, otherwise the concentration is too low and the hydrogel cannot be cross-linked after irradiation. The upper limit of the initial concentration is controlled by the solubility of the polymer.

[0043] Injectable tissue fillers usually also need to ensure a sufficiently long degradation time to achieve a long-term shaping effect. The degradation time is affected by the radiation dose and molecular weight. Generally speaking, when other conditions remain unchanged, the higher the radiation dose, the higher the degree of cross-linking, and the higher the molecular weight, the longer the degradation time of the hydrogel.

[0044] The injectable hydrogel provided by the present invention and its preparation method and application have the following beneficial effects:

[0045] 1. A new method for preparing injectable hydrogels is provided, which can transform non-injectable hydrogels prepared by cross-linking after irradiation into injectable hydrogels, and the properties of the injectable hydrogels are controllable, and they can be in liquid or solid state after being squeezed out by a needle;

[0046] 2. It was found that the injectable hydrogels prepared by different dilution treatments had different performances, and it was preferred to use a mixing syringe to push and mix evenly;

[0047] 3. Diluting the hydrogel by mixing it with a mixing syringe can ensure that the hydrogel does not need to go through the steps of removal, processing, canning, and sterilization after irradiation, but can be directly used as the final product and used with a tube of sterile water. This method ensures the cleanliness of the injectable hydrogel to the greatest extent, and is the simplest to operate, with low time consumption, low energy consumption, and green environmental protection;

[0048] 4. The hydrogel prepared by the preparation method has excellent physical and chemical properties (water retention, formability, degradation time, storage modulus and solid content) and stable batches, and is very suitable for the field of medical cosmetology. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0050] Figure 1 : Principle of irradiation cross-linking of glutamate

[0051] Figure 2 : Principles of chemical cross-linking of glutamate

[0052] Figure 3 :Comparison of sodium polyglutamate before and after irradiation; Figure A is sodium polyglutamate aqueous solution before irradiation, and Figure B is sodium polyglutamate hydrogel after irradiation; scale is 0.5 cm

[0053] Figure 4 :Water retention rate of irradiated cross-linked sodium polyglutamate hydrogel

[0054] Figure 5 :Water retention rate of chemically cross-linked sodium polyglutamate hydrogel

[0055] Figure 6 : Transmittance of sodium glutamate hydrogels obtained by different cross-linking methods

[0056] Figure 7 :Water retention rate of irradiated cross-linked carboxymethyl cellulose hydrogel

[0057] Figure 8 :Subcutaneous filling of rats after implantation of different hydrogels. Figure A shows sodium polyglutamate hydrogel implanted, and Figure B shows sodium hyaluronate hydrogel implanted

[0058] Fig. 9 :Sodium polyglutamate hydrogel formed under 20kGy (low) dose irradiation. Figure A shows the state of the hydrogel during injection, and Figure B shows the state of the hydrogel after in vitro injection

[0059] Fig.10 :Sodium polyglutamate hydrogel formed under 100kGy (higher) dose irradiation. Figure A shows the state of the hydrogel during injection, and Figure B shows the state of the hydrogel after in vitro injection. DETAILED DESCRIPTION

[0060] The preferred embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. Unless otherwise specified, the raw materials and equipment used in the following specific examples are all known products and are obtained by purchasing commercially available products.

[0061] Example 1: Preparation of injectable hydrogel

[0062] The present invention provides an injectable hydrogel and an optimal preparation method thereof as follows: sodium polyglutamate with a molecular weight of 2,000,000 is configured into a solution with a concentration of 10%, 1 mL is filled into a mixing syringe, sealed, and then irradiated with an electron beam of 100 kGy to obtain a non-injectable hydrogel. A new 5 mL mixing syringe is taken, 4 mL of water is filled, and the two mixing syringes are pushed against each other 30 times and mixed evenly to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle, has good formability after extrusion, will not collapse within 24 hours, and has a degradation time of more than 720 hours.

[0063] Example 2: Destroying the covalent bonds inside the non-injectable hydrogel is a necessary condition for preparing injectable hydrogels

[0064] The non-injectable hydrogel prepared in Example 1 was soaked in 5 times the mass of water to fully swell, and after the mass of the hydrogel remained unchanged, it was filled into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 10mL syringe needle, but cannot be injected and extruded through a 1mL syringe needle. It has good formability after extrusion, will not collapse within 5 hours, and has a degradation time of more than 720 hours. This result shows that if the hydrogel is only swollen without breaking, the hydrogel will not produce a thinning effect, that is, it cannot be directly used for injection.

[0065] Example 3: Effect of cross-linking method on hydrogel

[0066] Both irradiation and chemical crosslinking agents can crosslink sodium polyglutamate aqueous solution to obtain sodium polyglutamate hydrogel, but the reaction mechanisms of the two are different. Irradiation crosslinking forms free radicals, which connect the carboxyl and methylene groups in sodium polyglutamate to form a crosslinked network ( Figure 1 ); The mechanism of chemical cross-linking is to connect the carboxyl groups in sodium polyglutamate through small molecule cross-linking agents, thereby forming a cross-linked network ( Figure 2 In order to explore the effects of the above two cross-linking methods on hydrogels, this example uses sodium polyglutamate as raw material to prepare irradiated cross-linked sodium polyglutamate hydrogel ( Figure 3 ) and chemically cross-linked sodium polyglutamate hydrogel, the irradiation cross-linking method is the same as that described in Example 1, and the chemical cross-linking operation steps are described in reference (doi:10.3390 / polym14245505); and the water retention rate ( Figure 4-Figure 5 ) and transmittance ( Figure 6 ) for determination.

[0067] The method for determining water retention and light transmittance is as follows:

[0068] 1. Determination of water retention capacity: Take the fully swollen hydrogel, weigh it, and record the weight as W1. Then put it in an environment with a temperature of 298K and a humidity of 40%, and weigh it every 12 hours, and record the weight as W2. The water content at each time point is calculated as W2 / W1*100%. The performance of the hydrogel in slowing down the water loss in the environment is called water retention capacity.

[0069] 2. Determination of light transmittance: Use a stable incandescent lamp as the light source, place the hydrogel to be tested between the light source and the optical power meter, and record the reading T1 of the optical power meter. Remove the material to be tested and leave only the optical power meter. At this time, the reading of the optical power meter is T2. The light transmittance of the material is calculated to be T1 / T2*100%.

[0070] Depend on Figure 4 and Figure 5 It can be seen that the water content of both the hydrogel obtained by radiation cross-linking and the hydrogel obtained by chemical cross-linking decreased to varying degrees within 1.5 days, among which the water loss of the radiation cross-linked glutamic acid hydrogel was smaller, less than 40%, which was about 10% less than that of the chemical cross-linked hydrogel; within the next 1.5 days, the water content of the radiation cross-linked sodium polyglutamate hydrogel had stabilized, while the chemical cross-linked one still had a slow downward trend; until the third day, the water content of the radiation cross-linked sodium polyglutamate hydrogel was still as high as 60%, while that of the chemical cross-linked sodium polyglutamate hydrogel was only 40%. This is because the chemical cross-linking method for preparing sodium polyglutamate will cause the connections between glutamate molecules to occur on the carboxyl groups, and the resulting sodium polyglutamate hydrogel has relatively few free carboxyl groups; while in the radiation-cross-linked sodium polyglutamate hydrogel, more carboxyl groups are not involved in the cross-linking, and thus there are more free carboxyl groups, and the carboxyl groups have good hydrophilicity. Therefore, compared with chemically cross-linked sodium polyglutamate, the sodium polyglutamate obtained by radiation cross-linking has better water retention; a high water retention rate means better moisturizing and water-locking properties. When used as a medical beauty injection, it can maintain the filling effect for a longer time and keep the filled area elastic. This feature of radiation-cross-linked sodium polyglutamate hydrogel has great advantages in medical beauty filling applications.

[0071] Depend on Figure 6It can be seen that the transmittance of the sodium polyglutamate hydrogel obtained by radiation cross-linking is 5% to 10% higher than that obtained by chemical cross-linking. This is because the high-energy electron beam has a relatively good penetration ability, which can simultaneously promote the generation of free radicals in each region of the sodium polyglutamate aqueous solution and start cross-linking, so that the cross-linking of the hydrogel obtained is more uniform; while the chemical reaction always starts from the local area with a higher concentration of the chemical cross-linking agent, so the hydrogel obtained is less uniform. Therefore, compared with the polyglutamate hydrogel obtained by chemical cross-linking, the sodium polyglutamate hydrogel obtained by radiation cross-linking has higher transmittance. Injection products with high transmittance are more beautiful and highly accepted by users. In addition, transmittance is an indicator of the uniformity of the hydrogel, that is, the higher the transmittance, the more uniform the hydrogel, so after injection, the touch of the filled part can be guaranteed to be uniform. In addition, a fully cross-linked hydrogel can be obtained by irradiation for about 30 minutes. In contrast, chemical cross-linking of sodium polyglutamate usually requires more than 24 hours.

[0072] In summary, considering the water retention, light transmittance and preparation time, sodium polyglutamate hydrogel prepared by irradiation cross-linking is more suitable for tissue filler products.

[0073] Example 4: Effect of cross-linking partners on hydrogel properties

[0074] In addition to sodium polyglutamate, carboxymethyl cellulose can also be used to prepare hydrogels under irradiation crosslinking conditions. In order to explore the influence of the crosslinking object on the hydrogel, this example uses the irradiation method to prepare sodium polyglutamate hydrogel and carboxymethyl cellulose hydrogel. The specific operation steps are the same as those described in Example 1, except that the irradiation object is changed; and the water retention rate of the carboxymethyl cellulose hydrogel is measured. The measurement method is the same as that described in Example 3. The specific results are shown in Figure 7 .

[0075] Depend on Figure 7 It can be seen that the water retention of irradiated cross-linked carboxymethyl cellulose hydrogel is between that of irradiated cross-linked sodium polyglutamate hydrogel and chemical cross-linked sodium polyglutamate hydrogel, and the water loss in three days is 50%, which is about 10% more than that of irradiated cross-linked polyglutamic acid aqueous solution. This may be because carboxymethyl cellulose belongs to the polysaccharide structure, and there is a sugar ring structure with large steric hindrance in the molecular chain, which leads to a high viscosity of the carboxymethyl cellulose aqueous solution, and thus it is impossible to obtain a carboxymethyl cellulose aqueous solution with high solubility. Due to the low concentration, the carboxyl content in the final product is also low; on the other hand, during irradiation, sufficient cross-linking cannot occur in the carboxymethyl cellulose aqueous solution, and even the carboxymethyl cellulose hydrogel prepared under high irradiation dose conditions cannot be obtained by dilution to obtain an injectable hydrogel with good formability.

[0076] Sodium hyaluronate hydrogel is also a commonly used filler in medical cosmetology. In order to further compare the performance of sodium polyglutamate hydrogel and sodium hyaluronate hydrogel, this embodiment also conducted a subcutaneous injection experiment in rats, that is, 1 mL of sodium polyglutamate hydrogel and 1 mL of hyaluronic acid hydrogel were injected subcutaneously into rats, and the filling effect after injection was observed. The preparation method of sodium polyglutamate injectable hydrogel is the same as that described in Example 1, and the sodium hyaluronate hydrogel is prepared with reference to Chinese patent CN104761734B.

[0077] Depend on Figure 8 It can be seen that sodium polyglutamate hydrogel has better filling and molding effect. In summary, compared with the above two hydrogels, sodium polyglutamate hydrogel is more suitable for cosmetic filling.

[0078] Based on the above results, this example uses sodium polyglutamate as the basis and adds other polymers to optimize the properties of the resulting hydrogel. The preparation method and measurement method are the same as those described in Examples 1 and 3. The specific hydrogel components and properties are shown in Table 1.

[0079] Table 1 Comparison of properties of hydrogels formed by composite polymers

[0080]

[0081]

[0082] As shown in Table 1, adding some high molecular weight polymers to sodium polyglutamate can improve the performance of the gel to varying degrees, especially the water retention rate. This may be because the addition of other polymers further improves the cross-linking degree of the hydrogel network, among which the addition of sodium hyaluronate has the best effect.

[0083] Example 5: Effect of irradiation dose on the properties of sodium polyglutamate hydrogel

[0084] This example explores the effect of irradiation dose on sodium polyglutamate hydrogel. Except for the different irradiation intensities of the electron beam (20 / 40 / 100 / 150 / 200 kGy), the remaining operations are as described in Example 1. The fluidity and formability of the obtained hydrogels (samples 12 to 16) are then observed, and their degradation time is calculated. The specific results are shown in Table 2.

[0085] Table 2 Effects of different irradiation doses on the properties of sodium polyglutamate hydrogel

[0086]

[0087]

[0088] As shown in Table 2, with the increase of irradiation dose, the injectability and fluidity of sodium polyglutamate hydrogel weakened, on the contrary, the formability was enhanced and the degradation time was prolonged; Fig. 9 It can be seen that the hydrogel (sample 6) formed after low-dose (20 kGy) irradiation can pass through the needle of a 1 mL syringe and can form a droplet shape when squeezed out of the needle ( Fig. 9 A), while when injected into a culture dish in vitro, it has strong fluidity and average formability ( Fig. 9 B); On the contrary, although the hydrogel (sample 8) formed after irradiation with a higher dose (100 kGy) can also pass through the needle of a 1 mL syringe, the hydrogel squeezed out by the needle can form strips ( Fig.10 A), while no obvious flow occurs when injected into a culture dish in vitro ( Fig.10 B). This may be because the higher the irradiation dose, the higher the degree of cross-linking, which in turn leads to a more compact arrangement of molecules, so the self-cohesion of the hydrogel is stronger, the easier it is to maintain its shape, and the more difficult it is to degrade. However, considering the parameters such as injectability, fluidity, and formability, the optimal dose range of irradiated sodium polyglutamate hydrogel is 70-130kGy.

[0089] Example 6: Effect of molecular weight of sodium polyglutamate on sodium polyglutamate hydrogel

[0090] In this embodiment, sodium polyglutamate with a molecular weight of 700,000 is configured into a solution with a concentration of 10%, 1 mL is filled into a mixing syringe, sealed, and then irradiated with 100 kGy with an electron beam. Take another 5 mL mixing syringe, fill it with 4 mL of water, push the two mixing syringes against each other and mix them evenly to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle. It has good formability after extrusion, will not collapse within 24 hours, and the degradation time is less than 240 hours. Combined with the results of Example 5, the optimal molecular weight range of sodium polyglutamate used to prepare hydrogels is 700,000 to 2,000,000.

[0091] Example 7: Extrusion and sieving thinning

[0092] Sodium polyglutamate with a molecular weight of 2,000,000 is prepared into a solution with a concentration of 10%, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with an electron beam for 80 kGy. After the irradiated cross-linked hydrogel is squeezed and sieved using a 300-mesh sieve, 10 g of the sieved hydrogel is taken into 50 mL of water for magnetic stirring. After mixing evenly, fill it into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle. It has good formability after extrusion, will not collapse within 24 hours, and has a degradation time of more than 720 hours.

[0093] Example 8: Extrusion and sieving thinning

[0094] Sodium polyglutamate with a molecular weight of 700,000 was prepared into a 10% solution, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with 40 kGy of electron beam. The irradiated cross-linked hydrogel was squeezed and sieved using a 300-mesh sieve, and 10 g of the sieved hydrogel was added to 50 mL of water for magnetic stirring. After mixing evenly, it was filled into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle. It has good fluidity after extrusion and a degradation time of less than 120 hours.

[0095] Example 9: Extrusion and sieving thinning

[0096] Sodium polyglutamate with a molecular weight of 100,000 was prepared into a 10% solution, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with 40 kGy of electron beam. After the irradiated cross-linked hydrogel was squeezed and sieved using a 300-mesh sieve, 2 g of the sieved hydrogel was taken into 50 mL of water for magnetic stirring. After mixing evenly, it was filled into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle. After extrusion, the fluidity is excellent and the degradation time is less than 240 hours.

[0097] Example 10: Grinding and thinning after drying

[0098] Sodium polyglutamate with a molecular weight of 2,000,000 was prepared into a 10% solution, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with an electron beam for 80 kGy. The irradiated cross-linked hydrogel was placed in a 65°C oven and dried for 48 hours, and then ground. Take 2g of the ground hydrogel and add it to 40mL of water for magnetic stirring. After mixing evenly, fill it into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1mL syringe needle. It has good formability after extrusion, will not collapse within 5 hours, and has a degradation time of more than 720 hours.

[0099] Example 11: Grinding and thinning after drying

[0100] Sodium polyglutamate with a molecular weight of 100,000 is prepared into a solution with a concentration of 10%, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with an electron beam of 80 kGy. The irradiated cross-linked hydrogel is freeze-dried and then ground. Take 2g of the ground hydrogel and add it to 80mL of water for magnetic stirring. After mixing evenly, fill it into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1mL syringe needle. It has good formability after extrusion, will not collapse within 24 hours, and has a degradation time of more than 720 hours.

[0101] Example 12: Wet heat treatment thinning

[0102] Sodium polyglutamate with a molecular weight of 100,000 was prepared into a 10% solution, transferred to a culture dish with a diameter of 15 cm and sealed, and then irradiated with an electron beam for 80 kGy. The irradiated cross-linked hydrogel was sterilized by wet heat at 121°C for 8 minutes, and then 5 g of the wet heat treated hydrogel was added to 50 mL of water for magnetic stirring. After mixing evenly, it was filled into a syringe to obtain a hydrogel tissue filler. The filler can be injected and extruded through a 1 mL syringe needle, has good formability after extrusion, and has a degradation time of more than 720 hours.

[0103] Example 13: Comparison of thinning methods

[0104] In order to allow the hydrogel to be smoothly injected into the skin, a certain shear force needs to be applied to the prepared hydrogel to make the hydrogel flow more easily, and this process is called thinning. The thinning methods include thinning by mixing syringe, thinning by sieving and extruding, thinning by dry grinding, thinning by wet heat, etc. This example compares the storage modulus and solid content of injectable hydrogels prepared by different thinning methods. The storage modulus and solid content are determined as follows. The specific results are shown in Tables 3 and 4.

[0105] 1. Storage modulus detection method

[0106] Take the fully swollen hydrogel and use dynamic time scanning in Anton Paar MCR 302 rheometer, set the strain to 1%, the frequency to 10 rad / s, and each test lasts for 60 seconds;

[0107] 2. Solid content detection method

[0108] The fully swollen hydrogel was taken and weighed, and the weight was recorded as W1. The hydrogel was then freeze-dried and weighed, and the weight was recorded as W2. The solid content was calculated as W2 / W1*100%.

[0109] Table 3 Comparison of storage moduli of injectable hydrogels prepared by different thinning methods

[0110]

[0111] Table 4 Comparison of solid content of injectable hydrogels prepared by different thinning methods

[0112]

[0113] As shown in Tables 3 and 4, the CV values ​​of storage modulus and solid content of injectable hydrogels prepared by the drug-mixing syringe dilution method are significantly lower than those of hydrogels prepared by other dilution methods, indicating that the quality of the former is more stable between batches. This may be because the steps of this method are the simplest and are completely completed in a sealed syringe without the need for transfer, canning, etc., which is not easy to lose and easy to control quality.

[0114] In addition to providing energy to cross-link polymers, irradiation is also a widely recognized sterilization method. Therefore, the hydrogel cross-linked by irradiation meets the sterility standards. Diluting by mixing with a mixing syringe can ensure that the hydrogel does not need to go through the steps of removal, processing, canning, and sterilization after irradiation, but is directly used as the final product, and only needs to be used with a tube of sterile water. This method guarantees the cleanliness of the injectable hydrogel to the greatest extent, and the operation is the simplest, time-consuming, energy-saving, and environmentally friendly. On the contrary, although the hydrogel thinned by sieving extrusion, dry grinding, wet heat treatment and other methods can also be used for injection, due to too many processes, the physical and chemical properties of the injectable hydrogel obtained are not as stable as those obtained by diluting with a mixing syringe.

[0115] In summary, the drug mixing syringe dilution method is most suitable for the dilution of sodium polyglutamate hydrogel.

[0116] Although the present invention is disclosed as above, the present invention is not limited thereto. For example, it can be expanded according to its application range in medicine. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing an injectable hydrogel, characterized in that: The non-injectable hydrogel is thinned to prepare an injectable hydrogel; the non-injectable hydrogel is obtained by radiation cross-linking; the injectable hydrogel refers to a hydrogel that is in liquid state and can be extruded or injected through a needle, and the hydrogel can be in liquid or solid state after extrusion or injection; the non-injectable hydrogel refers to a hydrogel that is in solid state and cannot be extruded or injected through a needle.

2. The preparation method according to claim 1, characterized in that The thinning treatment includes crushing the non-injectable hydrogel and mixing it with water; the needle is a small-caliber needle, and the small-caliber needle is a needle with an inner diameter smaller than that of a 21G needle.

3. The preparation method according to claim 2, characterized in that: The non-injectable hydrogel is obtained by cross-linking a polymer aqueous solution through radiation.

4. The preparation method according to claim 3, characterized in that: The polymer includes one or more combinations of sodium polyglutamate, sodium hyaluronate, carboxymethyl cellulose, polyethylene oxide, sodium alginate, and sodium carboxymethyl starch.

5. The preparation method according to claim 4, characterized in that: The molecular weight of the sodium polyglutamate is 100,000-2,000,000; the molecular weight of sodium hyaluronate is 200,000-3,000,000; the molecular weight of carboxymethyl cellulose is 5,000-1,000,000; the molecular weight of polyethylene oxide is 50,000-1,000,000; the molecular weight of sodium alginate is 5,000-100,000; and the molecular weight of sodium carboxymethyl starch is 10,000-1,000,000.

6. The preparation method according to claim 5, characterized in that: The polymer includes sodium polyglutamate.

7. The preparation method according to claim 6, characterized in that: The concentration of the sodium polyglutamate aqueous solution is 5% to 50%, the concentration of the sodium hyaluronate aqueous solution is 5% to 15%, the concentration of the carboxymethyl cellulose aqueous solution is 2% to 30%, the concentration of the polyethylene oxide aqueous solution is 5% to 30%, the concentration of the sodium alginate aqueous solution is 2% to 10%, and the concentration of the sodium carboxymethyl starch aqueous solution is 5% to 30%.

8. The preparation method according to claim 7, characterized in that: Before radiation cross-linking, nitrogen needs to be introduced into the polymer aqueous solution to exhaust the oxygen in the polymer aqueous solution.

9. The preparation method according to claim 2, characterized in that: The radiation crosslinking is performed by electron beam irradiation or cobalt 60 irradiation.

10. The preparation method according to claim 9, characterized in that: The radiation cross-linking dosage is 5-200 kGy.

11. The preparation method according to claim 2, characterized in that: The method of thinning the non-injectable hydrogel includes one or more of the following: The first method: Use a mixing syringe to mix the non-injectable hydrogel and water in the mixer and push them together to mix evenly; The second method is to squeeze the non-injectable hydrogel through a sieve and then stir and mix it in water; The third method is to dry the non-injectable hydrogel, grind it, and then mix it with water; The fourth method is to sterilize the non-injectable hydrogel by wet heat sterilization and then stir and mix it evenly in water.

12. The preparation method according to claim 11, characterized in that: The volume ratio of the non-injectable hydrogel of the first, second or fourth type to water is 1:0.5-1:

10.

13. The preparation method according to claim 12, characterized in that: The mesh number of the second sieve is 50 meshes to 300 meshes.

14. The preparation method according to claim 13, characterized in that: The mass ratio of the third non-injectable hydrogel to water is 1:100-1:

20.

15. An injectable hydrogel, characterized in that The method is prepared by any one of claims 1 to 14.

16. Use of the injectable hydrogel according to claim 15 for preparing a hydrogel tissue filler.

Citation Information

Patent Citations

  • Radiation cross-linked collagen gel, and preparation method and usage method thereof

    CN103402489A

  • Sodium alginate and gelatin injectable dual-network hydrogel and preparation and application thereof

    CN107050510A

  • Injectable polysaccharide-based hot-melt gel bone filler and preparation method thereof

    CN114848918A

  • Injectable polysaccharide hydrogel as well as preparation method and application thereof

    CN116549714A

  • Cross-linked hydrogel microneedle for transdermal drug delivery and preparation method of cross-linked hydrogel microneedle

    CN117323286A